The Role of Video-Recorded Speaking Task in Improving Students’ Speaking Skill - Sakina, Rahma; Arifin, Riyadh Ahsanul; Mustika, Rispa; Mulyaningsih, Dini Utami (Ma'soem University, 2024)
This study is aimed at examining the effectiveness of video recorded speaking task in improving students’ speaking skill. A quasi-experimental design is employed in this study. The population was the tenth grade students of a vocational school in Bandung. The sample was 30 students chosen through convenience sampling. The sample was divided into two groups: experimental and control groups. Each group was given a pre-test at the beginning and a post-test at the end of the treatment. The kind of speaking test was mini conversation test where the researcher gave the students topic, and gave them time to prepare talks, and then they performed it in front of the class. In this stage, the researcher assessed their speaking skill using the scoring rubric by Brown (2001) cited in Vidhiasi (2017). The result of pre-test score showed that there was no significant difference between two classes. Then, the result of analyzing gained score, generated from the difference between pre- and post-test, revealed that the score of experimental class was significantly higher than controlled class at significance level 0,05. It means that the use of video recorded speaking task was effective in improving students’ speaking skill.